In vitro Organic Acid Production and In Vivo Food Pathogen Suppression by Probiotic S. thermophilus and L. bulgaricus - Evivie, Smith Etareri; Abdelazez, Amro; Li, Bailiang; Bian, Xin; Li, Wan; Du, Jincheng; Huo, Guicheng; Liu, Fei (Frontiers in Microbiology, 2019)
Foodborne pathogens are a major source of morbidity and mortality worldwide. For this cause, exploring various effective ways of suppressing their spread is at the forefront of many research projects. The current study aims to investigate the in vitro organic acid production of S. thermophilus KLDS 3.1003 and L. bulgaricus KLDS 1.0207 strains, their in vivo suppression of and immuno-modulatory effects against E. coli ATCC 25922 and S. aureus ATCC 25923 pathogens. First, lactic and acetic acid production using three carbon sources - 1% glucose (control), 1% sucrose and 1% fructo-oligosaccharides (FOS) - was determined by HPLC. For the in vivo section, a total of 40 BALB/c mice were purchased and divided into 10 treatment groups (control and 9 treatments). Animals were given one week to acclimatize and then fed treatment diets for 14 days. Afterwards, hematological (RBC, WBC, HB, PLT, Neutrophils, Eosinophils, Lymphocytes and Monocytes) and histopathological analyses were carried out. All analyses were done in triplicate. Results show that lactic and acetic acid productions for both strains increased with supplementation and were highest after 1% FOS addition. Regardless of carbon source, L. bulgaricus KLDS 1.0207 produced higher (P<0.05) amounts of lactic and acetic acids than S. thermophilus KLDS 3.1003. Also, generally better hematological parameters in probiotic groups than the control (P<0.05) were observed. In some instances, mice in probiotic treatment groups had better immunity levels (lymphocytes, monocytes, neutrophils, eosinophils) than those in the control and pathogen groups. Histopathological studies showed that no anomalies were associated with S. thermophilus KLDS 3.1003 and L. bulgaricus KLDS 1.0207 administration. In conclusion, S. thermophilus KLDS 3.1003 and L. bulgaricus KLDS 1.0207 strains are not only probiotic candidates but can have therapeutic applications.